STRATEGI KOMUNIKASI PUSAT PENGENDALIAN PEsMBANGUNAN EKOREGION SUMATERA DALAM MENSOSIALISASIKAN PROGRAM PEDULI LINGKUNGAN PADA USIA DINI - Kaspa, Yenni; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Caring for the environment is an attitude and action that seeks to prevent damage to the surrounding natural environment and develop efforts to repair the natural damage that has already occurred. Attitudes and actions must be taught from an early age so that it becomes a habit to be able to protect the environment. One of the efforts was carried out by the Sumatra Ecoregion Development Control Center by implementing an environmental care program at an early age. The socialization is carried out by giving material to school children so that they can apply the environmental care attitude that has been taught. This study aims to determine the communication strategy of the Sumatra Ecoregion Development Control Center in socializing environmental care programs at an early age.The research method used in this study is a qualitative research method. This qualitative research aims to explain the phenomenon as deeply as possible through data collection. Using a purposive technique by interviewing 12 informants who participated in an environmental awareness program at an early age conducted by the office of the Sumatra Ecoregion Development Control Center.The results of this study are the credibility of the communicator based on the knowledge and experience they have, the communicator in the socialization is the general staff and personnel who understand environmental issues. For the audience selected in the socialization were PAUD and kindergarten children in Pekanbaru City. The message strategy used is informative and persuasive by providing material on environmental issues and inviting children to behave in an environmentally caring manner. And the media strategy used in socialization is done by choosing face-to-face or direct media, print media such as books and leaflets and electronic media such as airing environmental films. The media used in the socialization were the results made by the office of the Sumatra Ecoregion Development Control Center and also the Ministry of Environment and Forestry.Keyword : Communication Strategy, Socializing, Environmental Care Programs, Early Age